SINTESIS SUPERKONDUKTOR SISTEM (Bi,Pb)Sr(Y,Ca)CuO BERFASE 1212 DENGAN METODE PELELEHAN - Sumadiyasa, M.; Rupiasih, Ni N.; Suardana, P. (BULETIN FISIKA; Vol 13 No 2 (2012): BULETIN FISIKA, 2012)
Superconductors system BPSCCO 1212 phase have been synthesized by solid state reaction with melting methods. The schedules: calcining at 900 0 C during 10 h, making of pellet, melting at 1010 0 C for 0.1 h, cooling (cooling rate 35 0 C/h) to 980 0 C, and sintering at 980 0 C during 5, 10, 20, and 30 h. From measurement of XRD, all of the sample has showed to be formed of  Bi-1212 phase. The highest volume fraction reach 91,23 % given by sample which is sintering at 980 0 C during 10 h. The spectrum pattern show reflection of its 00l extremely high intensity, showing the existence highly textured which as according to the typical behaviour for materials with the c-axis lying normal to the surface plane. The resistivity as function of temperature, that sample not yet shown the existence of Tc 0 , not yet had the superconducting properties at temperature above 77 K. The SEM shows morphology of surface, showing the existence of  the stacking of plate-like. Analyse EDX at some spots observation, show elements distribution of Bi, Pb, Sr, Y, Ca and Cu nearly homogenous, and its ratio of the spots on grain have been nearly the composition of 1212 phase.